ANALISIS TATA KELOLA RUANG TERBUKA HIJAU TERHADAP PEMBANGUNAN KOTA DI KABUPATEN MAJENE - Nurliah Nurliah; Muh. Syariat Tajuddin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
The research objective is to describe how the implementation of green open space governance in urban development in Majene Regency. This research uses descriptive analysis and explanation methods. In analyzing the data obtained, researchers used qualitative descriptive techniques that describe and explain the results of the study. The results showed that the implementation of green open space governance in Majene district is self-managed and is the responsibility of the Regional Work Units (SKPD) in charge of each green open space according to the criteria and types.